Graphite and Bismuth Selenide under Electrical Explosion in Confined Environment: Exfoliation, Phase Transition, and Surface Decoration. Issue 5 (19th January 2023) - Han, Ruoyu; Li, Chen; Gao, Ming; Cao, Yuchen; Yuan, Wei; Huang, Yifan
Abstract: Electrical explosion, characterized by ultrafast atomization and quenching rate (d T /d t  ≈ 10 10 –10 12 K s –1 ) of the sample, is a unique approach for "one‐step" synthesis of nanomaterials. Experiments are carried out with layered graphite and Bi2 Se3 under the action of electrical explosion in a confined reaction tube. High‐speed photography and electrophysical diagnostics are applied to characterize dynamic processes. SEM and EDS are used to characterize surface micro‐morphology of reaction products. The layered materials are first exfoliated to thin nanosheets/nanocrystals by shock waves and turbulent flow of the explosion. As the ionized explosion products (>10 000 K) contacts the sample, intense heat transfer happens, simultaneously atomizing the sample and quenching the plasmas. As a result, nanoparticles grow on the surface of thin sheets, forming "dot‐sheet" structure. The size distribution of the nanoparticles typically ranges from 10 to 100 nm, following Log‐normal distribution. The dotted graphite nanosheets gather together and form a stacked/cabbage‐like structure. By contrast, Bi2 Se3 case accompanies with chemical reactions, causing surface corrosion and showing more possibilities: nanocrystals and nanotubes growth on different areas of the sample. Abstract : The interactions between typical layered materials (graphite and Bi2 Se3 ) and electrical explosion metallic plasma are investigated from both physical and chemical perspectives for the first time in literature. Surface decoration processes including vapor deposition, metallization, and recrystallization are observed and related mechanisms analyzed in depth. Correlations between transient physical processes and resulting morphological characteristics are preliminarily ascertained, as shown below.